NONTUBERCULOUS TUBERCULOSIS CAUSED BY MYCOBACTERIUM GORDONAE - CLINICAL CASE REPORT - Gabriela Tsankova; Violina Kaludova; Tatina Todorova; Neli Ermenlieva; Emilia Georgieva (Peytchinski Publishing, 2015)
Background: Mycobacterium gordonae is a slow growing mycobacterium usually found in soil, tap water, and as laboratory contaminant. It is occasionally implicated in different infections in immunosuppressed patients. In contrast, there have been few case reports of active infection in immunocompetent individuals. Case Description: We report a case of a 46-old immunocompetent patient with long-term cough and poor expectoration. A computed tomography of the chest revealed punctiform lesions and fibrosis formation in the upper right lobe. It did not show any infiltrate in lung parenchyma. Mycobacterium gordonae was definitively diagnosed by genetic method. After antituberculosis treatment the toxic infectious syndrome was overcome. Conclusion: Mycobacterium gordonae is reported to cause clinically significant nontuberculosis infection in both immunocompetent and immunosuppressed individuals. Mycobacterium gordonae is hardly diagnosed with traditional laboratory methods, but the latest molecular techniques allow successful isolation and identification of slow growing Mycobacterium gordonae.